Stroke damages attentional maintenance in working memory. Issue 1 (8th August 2022) - Plancher, Gaën; Naëgelé, Bernadette; Guinet, Victoria; Portrat, Sophie; Colliot, Pascale
Abstract: Stroke is the main cause of acquired disability in adults, and specific deficits in working memory (WM) are among the most common cognitive consequences. In neuropsychological routine, WM is most of the time investigated in the framework of the multicomponent model (Baddeley & Hitch, 1974, The psychology of learning and motivation, 47). Using a more recent theoretical WM model, the time‐based resource‐sharing (TBRS) model (Barrouillet et al., 2011, Psychol . Rev ., 118, 175), the aim of the present study was to investigate in young post‐stroke patients to which extent attentional maintenance is impaired in WM. To address this question, we discarded other factors known to directly influence WM performance, that is processing speed and short‐term memory span. We proposed to 53 post‐stroke patients and to 63 healthy controls a complex span paradigm in which participants were asked to alternate between the memorization of a series of images and a concurrent parity judgement task of a series of digits. To investigate the attentional maintenance processes, we manipulated the cognitive load (CL) of the concurrent task. CL effect is typically interpreted as the involvement of attentional maintenance processes. The task was adapted to each participant according to their processing speed and memory span. As expected, the results showed higher recall performance in healthy controls compared with post‐stroke patients. Consistent with the literature, we also observed higher performance when the CL was low compared with high. However, the improvement in recall at low CL was smaller for post‐stroke patients compared with controls, suggesting that post‐stroke WM deficit could be in part due to a deficit of the attentional maintenance processes.